Therapeutic Effects of Wenxin Keli in Cardiovascular Diseases: An Experimental and Mechanism Overview - Tian, Guihua; Sun, Yang; Liu, Shuo; Li, Chengyu; Chen, Shiqi; Qiu, Ruijin; Zhang, Xiaoyu; Li, Youping; Li, Min; Shang, Hongcai (Frontiers in Pharmacology, 2018)
Cardiovascular diseases (CVDs) are the major public health problem and a leading cause of morbidity and mortality on a global basis. Wenxin Keli (WXKL), a formally classical Chinese patent medicine with obvious efficacy and favorable safety, plays a great role in the management of patients with CVDs. Accumulating evidence from various animal and cell studies has showed that WXKL could protect myocardium and anti-arrhythmia against CVDs. WXKL exhibited its cardioprotective roles by inhibiting inflammatory reaction, decreasing oxidative stress, regulating vasomotor disorders, lowering cell apoptosis, and protection against endothelial injure, myocardial ischemia, cardiac fibrosis and cardiac hypertrophy. Besides, WXKL could effectively shorten the QRS and Q-T intervals, decrease the incidence of atrial/ ventricular fibrillation and the number of ventricular tachycardia episodes, improve the severity of arrhythmias by regulating various ion channels with different potencies, mainly comprising peak sodium current (INa), late sodium current (INaL), transient outward potassium current (Ito), L-type calcium current (ICaL) and pacemaker current (If).